Quantitative variations in the essential oil of Minthostachys mollis (Kunth.) Griseb., in response to insects with different feeding habits - Banchio, Erika (2005)
Plants display a diverse array of inducible changes in secondary metabolites following insect herbivory. Herbivores differ in their feeding behavior, physilogy, and mode of attachment to the leaf surface, and such variations might be reflected in the induced responses of damaged plants. Induced changes were analyzed for Minthostachys mollis, a Lamiaceae with medicinal and aromatic uses, and four species fo folivore insects with different feeding habits (chewing, scrapin, sap sucking, and puncturing). In M. mollis leaves experimentally exposed to the insects, levels of the tow dominant monoterpenes pulegone and menthone were assessed 24 and 48 h after wounding. Menthone content  generally decreased in the essential oil of damaged leaves, whereas pulegone concentration increased in all treatments. These changes occurred also in the adjacent undamaged leaves, suggestinga systemic response. The relatively uniform response to different kinds of damage could be attributable to the presence of such a strongly active compound as pulegone in the essential oil of M. mollis. The effects of wounding on essential oil concentration may be significant from a commercial point of view.